2008
DOI: 10.4103/0970-2113.59596
|View full text |Cite
|
Sign up to set email alerts
|

Unusual presentation of an uncommon lung malignancy

Abstract: Combined type of small cell lung carcinoma (SCLC) is a rare malignancy of the lung that is usually peripheral and diagnosed after resection. We report an unusual case of centrally located combined SCLC with squamous cell component that was diagnosed on endobronchial lung biopsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…In this cell type, polypoid lesions with a rough surface covered with necrotic material are the most predominant lesions (16,17). Although SCLC with endobronchial growth is extremely rare, specific cases have been reported (18,19). Ramaraju et al reported an unusual case of centrally-located combined SCLC with a squamous cell component, which was diagnosed by an endo-bronchial lung biopsy (18).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this cell type, polypoid lesions with a rough surface covered with necrotic material are the most predominant lesions (16,17). Although SCLC with endobronchial growth is extremely rare, specific cases have been reported (18,19). Ramaraju et al reported an unusual case of centrally-located combined SCLC with a squamous cell component, which was diagnosed by an endo-bronchial lung biopsy (18).…”
Section: Discussionmentioning
confidence: 99%
“…Although SCLC with endobronchial growth is extremely rare, specific cases have been reported (18,19). Ramaraju et al reported an unusual case of centrally-located combined SCLC with a squamous cell component, which was diagnosed by an endo-bronchial lung biopsy (18). In addition, Lee et al presented the case of a 51-year-old male with SCLC and an endobronchial mass in the left main bronchus (19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation